1064‐nm‐resonant gold nanorods for photoacoustic theranostics within permissible exposure limits. Issue 10 (2nd June 2019) - Cavigli, Lucia; Centi, Sonia; Borri, Claudia; Tortoli, Paolo; Panettieri, Ilaria; Streit, Ingolf; Ciofini, Daniele; Magni, Giada; Rossi, Francesca; Siano, Salvatore; Ratto, Fulvio; Pini, Roberto
Abstract: Therapeutic and diagnostic methods based on photomechanical effects are attracting much current attention in contexts as oncology, cardiology and vascular surgery, for such applications as photoacoustic imaging or microsurgery. Their underlying mechanism is the generation of ultrasound or cavitation from the interaction of short optical pulses with endogenous dyes or targeted contrast agents. Among the latter, gold nanorods are outstanding candidates, but their use has mainly been reported for photoacoustic imaging and photothermal treatments. Conversely, much less is still known about their value as a precision tool for photomechanical manipulations, such as to impart local damage with high spatial resolution through the expansion and collapse of microbubbles. Here, we address the feasibility of gold nanorods exhibiting a distribution of surface plasmon resonances between about 900 to above 1100 nm as a contrast agent for photoacoustic theranostics. After testing their cytotoxicity and cellular uptake, we discuss their photostability and use to mediate cavitation and the photomechanical destruction of targeted cells. We find that the choice of a plasmonic band peaking around 1064 nm is key to enhance the translational potential of this approach. With respect to the standard alternative of 800 nm, at 1064 nm, relevant regulations on optical exposure are less restrictive and the photonic technology is more mature. Abstract : The use of longer‐than‐standard gold nanorods with a plasmonic band around 1064 enables the generation of photoacoustic signals and the onset of cell‐killing photocavitation within maximum permissible exposure limits.